PENGARUH KITOSAN DARI CANGKANG UDANG TERHADAP RED BLOOD CELL, HEMOGLOBIN, DAN TROMBOSIT PADA MODEL RHEUMATOID ARTHRITIS YANG DIINDUKSI CFA - Sah Putra, Suyandra; Darmawan, Endang (Universitas Ahmad Dahlan, 2015)
The research was conducted the effect of chitosan on rats blood alteration that induced arthtritis. In addition, the research used pre-post test group control design. than used Â was divided into groups (n=6) including normal groups, positive control, negatif control, and Â groups were treated byÂ khitosan at varian 50 mg/200gBB and 100 mg/200gBB doses. Adjuvant-induced was developed using complete Freundâs Adjuvant on 1st day, than 17-47th days after treated given appropriate their groups. To evaluate did blodd counter on 0, 16th,and 47th days after treated with otomatic optic dan electronic resisten method. Than analyzed using ANOVA test and paired t-test (p<0,05). Result of the research is Chitosan 50 mg/200gBW fit to reduce of eritrocid 6,1% (p<0,05), hemoglobin 7,77% (p<0,05) and PLCR 35,29% (p<0,05), meanwhile of Chitosan 100 mg/200gBW fit to reduce of trombocyte 40,49% (p>0,05) and PLCR 35,66% (p<0,05). In additional research, khitosan 50 mg/200gBW fit to complete blood of the rheumatoid arthritic mouse well.